Reclamação constitucional : natureza jurídica, algumas hipóteses polêmicas de cabimento e necessidade da medida excepcional - Leite, Henrique de Andrade (2010)
The constitutional complaint is a procedural measure provided for in the Federal Constitution. Its purpose is to preserve the competence and guarantee of authority of the decisions of the Supreme Federal Court (STF) and Superior Court of Justice (STJ). The objective of this work is to analyze this procedural institute, specifically in terms of the more polemic and important issues surrounding it. The history of the constitutional complaint, through its successive phases, shows signs that it emerged out of a need perceived, by the Federal Supreme Court, for an instrument that would preserve its competence and ensure effective compliance with its decisions, which indicates reluctance among the judges and the courts that submit to its jurisdiction. From the origins of the complaint, it discusses its legal nature, which went from being an exercise of the right to petition the Public Authorities, at its outset, to an autonomous, constitutional action, when the current Constitution came into force. Despite the stalemate that still exists, particularly in regard to the recent understanding adopted by the STF that the complaint is an exercise of the right to petition, the best conclusion is that it assumes characteristics inherent to the action, this being its nature. Considered as an action, the complaint, contrary to the decision of the STF, cannot be extended to the State Constitutions, as the Union holds the private competence to legislate a procedural law. Furthermore, the courts already have sufficient mechanisms in procedural law to preserve the competence and guarantee of authority of their decisions, therefore the complaint, at State level, besides being unconstitutional, is also unnecessary. On the contrary, the complaint is both constitutional and necessary for the STJ, against decisions of the special state courts that fail to respect its jurisprudential guidance relative to the interpretation of the federal law. The complaint is also appropriate in the case of the decision that prevents the interlocutory appeal filed against undue dismissal and against the declaration of damage to the extraordinary appeal by the Court of origin from becoming final and unappealable, based on the examination of general repercussions and of the merit of the appeal held as a paradigm. The complaint is only constitutional when judged in the STF and STJ. In the Superior Military Court (STM), before which it is appropriate since it is determined by federal law, it is only a complaint, despite having identical objectives. In relation to the other courts, i.e. the Superior Labor Court (TST), Superior Electoral Court (TSE) and Regional Federal court (TRF), the complaint, although regulated by internal regimens or resolutions, is unconstitutional, since there is no constitutional discipline or a federal law that institutes it. The complaint may be replaced by the existing mechanisms for the preservation of competence, for this specific function. The need is emphasized for a measure that seeks to guarantee the fulfillment of decisions for which non-compliance should not be considered, even more so in relation to the STF and STJ, which are of such importance in the constitutional model adopted. Currently, a risk to the jurisdictional provision of the STF is emerging, which needs to be evaluated, namely, the likelihood of a further increase in its already significant workload, due to the possibility of constitutional complaint against the act of judicial or administrative authority that disrespects the binding precedent. A solution needs to be found quickly, and put into practice, before the court is transformed into a court of first instance. But one cannot hold the procedural institute responsible, in itself, for the evils it carries. The constitutional complaint exists because it was deemed necessary, and continues to be necessary today. Worthy of deeper reflection, it is the disrespect of the legal decisions in Brazil that demonstrates an affront to the principles and regulations established by the Constitution.